Respuesta :

This is my answer. Check it!

Answered by Benjemin

Ver imagen Аноним

Answer:

  • See below

Step-by-step explanation:

Let us have:

  • a - the first term
  • r - common ratio
  • l - the last term

Formula of nth or last term:

  • l = arⁿ⁻¹

The sequence:

  • a, ar, ar², ..., arⁿ⁻¹

The sum of the sequence is:

  • S = a + ar + ar² + ... + arⁿ⁻¹

Lets multiply the sum by r and subtract the sum:

  • rS = ar + ar² + ar³ + ... + arⁿ
  • S = a + ar + ar² + ... + arⁿ⁻¹
  • rS - S = arⁿ - a = r(arⁿ⁻¹) - a = lr - a

Solve this for S:

  • S(r - 1) = lr - a
  • S = (lr - a)/(r - 1)

So we have a sum formula determined by the first, last terms and the common ratio.

ACCESS MORE